Memórias no cárcere : valência e especificidade na evocação autobiográfica de Pessoas Privadas de Liberdade (PPLs) - Silva, Gisele Menezes da (2023)
Autobiographical memory (AM) is a term that refers to a person's recollection of events from their lives. It typically functions to contribute to identity stability, goal achievement, well-being promotion, and the establishment of bonds. It provides a reference for who we are and our achievements and misfortunes to be replicated or avoided. Considering that social isolation can lead to interpersonal relationship dysfunctions and emotional deficiencies, individuals in incarceration may exhibit alterations in AM. The aim of this study was to investigate the characteristics of autobiographical memory in incarcerated individuals. Seventy male volunteers between the ages of 18 and 45 were recruited and divided into two groups: Group 1 (incarcerated men) and Group 2 (free men with no history of incarceration). Group 1 volunteers were recruited from a semi-open correctional facility, while Group 2 participants were invited from public schools offering Adult and Youth Education (EJA). All volunteers completed a sociodemographic questionnaire, the Depression, Anxiety, and Stress Scale (DASS-21), the Self-Assessment Manikin (SAM) scales, the Levenson Self-Report Psychopathy scale, and the Autobiographical Memory Test (AMT). The results highlight three main conclusions: firstly, being incarcerated in a semi-open regime does not necessarily result in impairments in AM recall; secondly, involvement in educational, leisure, sports or occupational activities can assist in emotional regulation and concurrently in the proper functioning of AM mnemonic processes; thirdly, there may be a cognitive reappraisal process in the face of life adversities, which offered more satisfaction regarding negative life memories. Future studies may investigate the relationship of individuals in penal institutions with leisure activities, sports and faith.